How ATP inhibits the open K(ATP) channel. - Craig, T; Ashcroft, F; Proks, P (2008)
ATP-sensitive potassium (K(ATP)) channels are composed of four pore-forming Kir6.2 subunits and four regulatory SUR1 subunits. Binding of ATP to Kir6.2 leads to inhibition of channel activity. Because there are four subunits and thus four ATP-binding sites, four binding events are possible. ATP binds to both the open and closed states of the channel and produces a decrease in the mean open time, a reduction in the mean burst duration, and an increase in the frequency and duration of the interburst closed states. Here, we investigate the mechanism of interaction of ATP with the open state of the channel by analyzing the single-channel kinetics of concatenated Kir6.2 tetramers containing from zero to four mutated Kir6.2 subunits that possess an impaired ATP-binding site. We show that the ATP-dependent decrease in the mean burst duration is well described by a Monod-Wyman-Changeux model in which channel closing is produced by all four subunits acting in a single concerted step. The data are inconsistent with a Hodgkin-Huxley model (four independent steps) or a dimer model (two independent dimers). When the channel is open, ATP binds to a single ATP-binding site with a dissociation constant of 300 microM.